(untitled) (Fiep Bulletin - online, 2019)
In order to understand how the relationship between public health policies of the elderly and their effectiveness withthe population occurs, we analyze the public policies focused on the health of the elderly, their laws, compliance andeffectiveness with the population. This research project was carried out through a bibliographical research and a field survey,carried out in two spaces, one public and one private, with (n) sample equal to 10 elderly people in each space visited. Weperformed a general anamnesis where the following variables were collected: gender, age, weekly frequency and effects fromphysical exercise practice. We performed an anamnesis to detect preexisting diseases such as: diabetics, hypertension, andbody pains from joint inflammation (arthritis, arthrosis, rheumatism, fibromyalgia) and / or spine. We observed the followingresults: 20-30% of the sample in the two spaces were diabetic, 50-70% hypertensive, 70-100% presented body pains, age 60-75,women became 90% of public space visitors and 80% of the participants in the private space, the sample reported attending thespaces from 1 to 5 times a week and 100% of the sample reported having obtained some kind of benefit through physicalexercise, the lower percentiles refer to the private space , which as observed has lower pathological indexes than the public. Therelationship between the public health policies of the elderly and their effectiveness with the population occurs in a promotionalway, with subsequent public neglect.